2011
DOI: 10.1002/hbm.21235
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable neural imprints of perception and grammar in auditory functional imaging

Abstract: In language processing, the relative contribution of early sensory and higher cognitive brain areas is still an open issue. A recent controversial hypothesis proposes that sensory cortices show sensitivity to syntactic processes, whereas other studies suggest a wider neural network outside sensory regions. The goal of the current event-related fMRI study is to clarify the contribution of sensory cortices in auditory syntactic processing in a 2 × 2 design. Two-word utterances were presented auditorily and varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 63 publications
7
43
0
Order By: Relevance
“…Similar reasoning applies to other studies that have targeted syntactic processing and reported effects only in the inferior frontal and posterior temporal regions (e.g., syntactic violation manipulations : Embick, Marantz, Miyashita, O’Neil, & Sakai, 2000; Cooke et al , 2006; Friederici, Kotz, Scott, & Obleser, 2010; Herrmann, Obleser, Kalberlah, Haynes, & Friederici, 2012; or syntactic priming : Santi & Grodzinsky, 2010; Menenti, Segaert, & Hagoort, 2012; Segaert, Menenti, Weber, Petersson, & Hagoort, 2012). We hypothesize that those effects (and possibly other, non-syntactic, effects; e.g., Devlin et al , 2000), like the syntactic complexity effects studied here, are actually present throughout the language system.…”
Section: Discussionsupporting
confidence: 70%
“…Similar reasoning applies to other studies that have targeted syntactic processing and reported effects only in the inferior frontal and posterior temporal regions (e.g., syntactic violation manipulations : Embick, Marantz, Miyashita, O’Neil, & Sakai, 2000; Cooke et al , 2006; Friederici, Kotz, Scott, & Obleser, 2010; Herrmann, Obleser, Kalberlah, Haynes, & Friederici, 2012; or syntactic priming : Santi & Grodzinsky, 2010; Menenti, Segaert, & Hagoort, 2012; Segaert, Menenti, Weber, Petersson, & Hagoort, 2012). We hypothesize that those effects (and possibly other, non-syntactic, effects; e.g., Devlin et al , 2000), like the syntactic complexity effects studied here, are actually present throughout the language system.…”
Section: Discussionsupporting
confidence: 70%
“…The technique has also been generalized to incorporate multiple classes to test more complex representational models (e.g., representational similarity analysis; Kriegeskorte, Mur, & Bandettini, 2008). It has been used to examine neural coding of a wide range of different task events including aspects of stimuli, task rules, participant responses, rewards, emotion, and language (e.g., McNamee, Rangel, & O'Doherty, 2013;Herrmann, Obleser, Kalberlah, Haynes, & Friederici, 2012;Woolgar, Thompson, Bor, & Duncan, 2011;Peelen & Vuilleumier, 2010;Haxby et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Applications of the MVPA have rapidly developed, covering studies of neuronal mechanisms in various domains, such as perception [12][13][14][15][16][17] , learning and memory [18][19][20][21] , language [22] , intention [23] , decision-making [5,[24][25][26] , emotion [27][28][29][30] , and mental disorders [31][32][33] . Instead of serving as a tutorial on applying multivariate classifiers to fMRI data (see Pereira et al [34] , an excellent reference for this purpose), this review attempts to give a general introduction to recent promising developments branching off from the original idea of treating fMRI data as multivariate patterns.…”
Section: Unlike Conventional Glm-based Brain Mappingmentioning
confidence: 99%
“…Exploiting its information-mapping nature, a number of studies have applied this approach to a vast range of research topics [15,16,22,25,26,30,[58][59][60][61][62][63][64] . On the other hand, searchlight MVPA can be considered as a featureselection method that reflects which voxels (features) are most informative in distinguishing stimuli (see 'Section 7 Summary of MVPA algorithms and parameters').…”
Section: Searchlight Mvpamentioning
confidence: 99%